lim ln[1+kx)] x-->inf.

Let us rewrite 1 as x/x

==> lim ln(x/x +kx) = lim ln[(1/x)(x)+kx

Now factor x

= lim ln x[(1/x)+k]

we know that ln xy= ln x + ln

==> lim lnx + lim ln [(1/x)+k]}

when x--> inf ==> lnx= inf

==> ln(1/x) +K =...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

lim ln[1+kx)] x-->inf.

Let us rewrite 1 as x/x

==> lim ln(x/x +kx) = lim ln[(1/x)(x)+kx

Now factor x

= lim ln x[(1/x)+k]

we know that ln xy= ln x + ln

==> lim lnx + lim ln [(1/x)+k]}

when x--> inf ==> lnx= inf

==> ln(1/x) +K = ln k

==> infinity +ln K = inf.

The limit is inf.

Also we need to know that ln(1+kx) is defined when kx> -1